2020
DOI: 10.1007/s13300-020-00882-2
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulation Differences in the Cardiovascular Efficacy of Long-Acting Glucagon-Like Peptide 1 Receptor Agonists in Type 2 Diabetes Mellitus: A Systematic Review and Meta-analysis

Abstract: Introduction: The cardiovascular efficacy of glucagon-like peptide 1 receptor agonists (GLP-1RAs) in type 2 diabetes mellitus (T2DM) are well documented; however, the differences in cardiovascular efficacy among subpopulations remain unknown. This systematic review and meta-analysis aimed to explore the differences in cardiovascular efficacy of long-acting GLP-1RAs among subpopulations of patients with T2DM and to assess the drug safety. Methods: Relevant studies up to March 31, 2020 were searched for in six e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“… History of CVD 3 105 107 8 125 , 162 167 7 83 , 90 95 , 98 , 99 4 104 – 106 , 109 3 86 , 168 , 169 5 2 , 80 , 83 , 95 , 112 No consistent impact on SGLT2i or GLP1-RA outcomes. Age 2 107 , 108 3 121 , 165 , 170 3 83 , 92 , 94 2 104 , 109 1 171 4 78 80 , 83 No consistent heterogeneity by age for SGLT2is; No evidence of age effect for GLP1-RAs. Sex 3 102 , 107 , 108 1 165 5 83 , 90 , 92 , 94 , 96 , 99 4 102 , ...…”
Section: Resultsmentioning
confidence: 99%
“… History of CVD 3 105 107 8 125 , 162 167 7 83 , 90 95 , 98 , 99 4 104 – 106 , 109 3 86 , 168 , 169 5 2 , 80 , 83 , 95 , 112 No consistent impact on SGLT2i or GLP1-RA outcomes. Age 2 107 , 108 3 121 , 165 , 170 3 83 , 92 , 94 2 104 , 109 1 171 4 78 80 , 83 No consistent heterogeneity by age for SGLT2is; No evidence of age effect for GLP1-RAs. Sex 3 102 , 107 , 108 1 165 5 83 , 90 , 92 , 94 , 96 , 99 4 102 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A similar meta-analysis reported that the glucose-lowering effectiveness seemed to be similar among Asian people and people who are not Asian regardless of baseline weight 208 . Previous meta-analyses comparing cardiovascular risk reduction among Asian people and people who are not Asian reported mixed findings 209,210 , but an updated meta-analysis of six cardiovascular outcome trials for GLP1 receptor agonists reported that reductions in major adverse cardiovascular events were greater among Asian people than in white people 202 . Emerging evidence suggests that GLP1 receptor agonists could be more effective when initiated early in the course of disease among people with adequate β-cell function 211 .…”
Section: Glp1 Receptor Agonistsmentioning
confidence: 99%
“…Analysis of these findings entails limitations that stem from the fact that results were based on adverse events reports and subsequent precise evaluation was not performed. Causal relationship between DR risk and the use of GLP-1 agonists was not confirmed in further meta-analyses [ 43 , 44 , 45 , 46 ]. In an AngioSafe study, designed to determine the safety of GLP-1 RAs in the retina, in both clinical models with liraglutide and experimental models with exenatide, negative effects on retinal angiogenesis and severe DR were not confirmed [ 47 ].…”
Section: Resultsmentioning
confidence: 97%